Analytical and numerical approaches to predict the flow characteristics of a magnetorheological fluid in rotational symmetric cross sections - Rösel, Sebastian; Merklein, Marion; Grüner, Martin (Key Engineering Materials, 2012)
For a better understanding of the hydroforming process using magnetorheological fluids as a medium it is necessary to gain basic information for an analytical and numerical description of the fluid behaviour under process relevant conditions. Therefore an experimental setup is build up, which consists of a pressure chamber and a rotational symmetric outlet. Different parameters like feed rate and magnetic flux density are varied. Afterwards an analytical approach and a numerical model are developed. To get the relevant material input data for the fluid description an additional numerical simulation of the created magnetic flux density with flux lines perpendicular to the symmetry line of the outlet is performed. The leakage rates, which are observed for the experiments, are compared to the analytically calculated ones and to the results of the numerical simulation. © (2012) Trans Tech Publications.
LFT Import::2019-07-29 (1803)
Keywords: Active fluid media; Hydroforming; Magnetorheological fluid (MR-Fluid); Sheet metal forming

Characterization of a magnetorheological fluid and simulative design of a magnetic field with respect to its suitability for hydroforming - Rösel, Sebastian; Merklein, Marion (Proceedings of the 5th International Conference on ADVANCES IN PRODUCTION ENGINEERING, 2010)
LFT Import::2019-08-05 (140)

Characterization of a Magnetorheological Fluid with Respect to its Suitability for Hydroforming - Rösel, Sebastian; Merklein, Marion (International Journal of Material Forming, 2010)
Nowadays the global warming and the shortage of resources represent big challenges. To cope with these deviances it is the duty of the automotive industry, to build up light weight constructions for high efficient vehicles. For example forming parts as components of exhaust systems or chassis components could be realized by hydroforming, a new flexible technology, which enables the realisation of undercuts and increases the forming limits. Thereby comparatively complex part geometries can be produced. Using this process the blank is deformed by gases or fluids as pressure media. In this case a magnetorheological fluid could be used. The key property of magnetorheological media is an increasing viscosity under magnetic fields. Thus they can not only serve as a pressure medium, but also act as a sealing in the flange area to prevent leakage. For a better understanding of the process a basic characterisation has to be done. Therefore an experimental setup is built up. Different parameters like feed rate and magnetic flux density are varied to get information about the behaviour of the tested fluid. The achievable cavity pressure is perhaps the most important parameter, because it determines the geometry of the part at the end of the forming step, especially at the small radii of the component. Another result of these tests is the fundamental potential of magnetorheological fluids for the process of hydroforming of blanks. © 2010 Springer-Verlag France.
LFT Import::2019-07-29 (137)
Keywords: Forming technology; Hydroforming; Magnetorheological fluid

Enhancing Forming Limits by Using a Magnetorheological Fluid as Active Fluid Medium for Hydroforming - Rösel, Sebastian; Merklein, Marion (Steel research international: Special Edition: 10th International Conference on Technology of Plasticity, 2011)
The automobile industry has to preserve commodities by light weight constructions. It is to the forming technology to overcome the challenges of forming high complex part geometries, by offering more flexible forming technologies e.g. hydroforming, which are cost efficient and can utilize the whole formability of the used materials. One active deviance, which has prevented the application of hydroforming of blanks In serial production, is the sealing of the cavity In the flange area. To Insure a complete sealing, it Is necessary to remain below a defined ratio between cavity pressure and contact pressure In the flange area, which Is restricting the process window. This experimental work focuses on the Influence of the magnetorheological fluid Basonetic 5030 on the sealing ratio compared to mineral oil shell tellus 100. Experiments are carried out at different cavity and contact pressures with the media mentioned above. Additionally a defined magnetic flux density Is applied to the magnetorheological fluid In the flange area to Increase its viscosity. Afterwards cups are drawn with DC04 of a sheet thickness of 1 mm and the resulting cup geometries are measured. Various geometric parameters are compared to each other to identify the process latitudes and the possible process parameters. © 2011 Wiley-VCH Verlag GmbH & Co. KGaA. Weinheim.
LFT Import::2019-08-05 (1650)
Keywords: Forming processes; Hydroforming; Magnetorheological fluid (MRF); Sheet metal

Enhancing Process Limits of Blank Hydroforming - Merklein, Marion; Grüner, Martin; Rösel, Sebastian (Internationale Konferenz „Hydroumformung von Blechen, Rohren und Profilen“, 2012)
LFT Import::2019-08-05 (1813)

Flow behaviour of magnetorheological fluids, considering the challenge of sealing in blank hydroforming in the flange area with rectangular leakage area cross-sections - Rösel, Sebastian; Merklein, Marion (Key Engineering Materials, 2011)
The need of light weight constructions and parts with tailored or even more homogeneous mechanical properties especially for structural components leads to the use of alternative forming technologies. These forming processes like sheet metal hydroforming are established to gain more flexibility and to increase the forming limits. But to apply this forming technology successfully, it is necessary to overcome some obstacles. One typical challenge for hydroforming of blanks, which has prevented further application of this technology, is the sealing of the cavity in the flange area. Nowadays there are a lot of basic approaches to accomplish a sealing in this tool area. Commonly a sealing can be reached by increasing the contact pressure in the outer region of the blank. This approach reduces the possible blank draw in and hence abates the possible realisation of complex part geometries. One possible approach to increase the ratio between cavity pressure and contact pressure in the flange area is the choice of a capable active fluid medium. The aim is to reduce the contact pressure in the flange area and nevertheless ensure a complete sealing. In this case the magnetorheological fluid (MR-fluid) BASF Basonetic 5030 is used as a pressure medium for hydroforming. For characterizing this fluid under different amounts of magnetic flux density and in comparison to a common hydraulic medium, an experimental setup was built up to gain process relevant data for hydroforming processes. Therefore different experiments were carried out with different media and different flux densities for the MR-fluid. To get more information about the mode of action and the accessible amounts of cavity pressure and related contact pressures in the flange area, these two process parameters were varied. © (2011) Trans Tech Publications.
LFT Import::2019-07-29 (1635)
Keywords: Active fluid media; Hydroforming; Magnetorheological fluid (MR-fluid); Sheet metal forming

Praxisnahe Versagensbeschreibung in der Blechumformung - Vergleich zwischen dem mikromechanischen Schädigungsmodell nach Gurson-Tveergard-Needleman und dem Grenzformänderungsschaubild - Gröbel, Daniel; Rösel, Sebastian; Merklein, Marion; Butz, A. (Umformen, Schneiden, Verbinden im Leichtbau - Machbarkeit - Produktivität - Qualität - Tagungsband T36 des 33. EFB-Kolloquiums Blechverarbeitung am 16. und 17. April 2013 in Fellbach, 2013)
LFT Import::2019-08-05 (1889)

Wirkmedienbasierte Umformung von Blechhalbzeugen unter Anwendung magnetorheologischer Flüssigkeiten als kombiniertes Wirk- und Dichtmedium - Rösel, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
The objective of these investigations is to enhance the process window of blank hydroforming processes to increase the robustness and the forming possibilities. This aim shall be reached by using a magnetorheological fluid as active fluid medium. If it is possible to shift the sealing limit to higher cavity pressures and lower flange contact pressures the necessary investment and the blankholder force can be decreased. Thereby an extensive use of this technology becomes possibl